Hibah as instrument in Islamic financial planning: the understanding level of hibah planning towards UiTM staff / Nurain Najihah Jasrudin - Jasrudin, Nurain Najihah (2019)
Sometimes the distribution of the property of the Muslim through faraid can lead to some issues if it is not properly administered and fully understood. The distribution of Muslim properties is estimated worth around RM42 billion in Malaysia is believed to remain unresolved. The possibility of the estate's failure to settle will result in a number of negative legal, cultural, social and religious consequences. Previous findings have shown that people in this country lack the ability to carefully plan wealth distribution, particularly in future planning. As a result, they are fully dependent on the faraid inheritance system of property division. Therefore, it is necessary to correct immediately the public perception that the property can only be distributed through the farāid. Alternatively planning the distribution of property by hibah (gift inter vivos) during one's lifetime must be increased as it is obviously beneficial to the Muslim community. The legal framework is not only intended to ensure the successful implementation of hibah in Malaysia, it also needs to be clarified in order to overcome certain statutory non-statutory and technical obstacles to the implementation of hibah. This research is based on qualitative research and the approach that will be used is the primary data which is using the questionnaire. A survey via questionnaire is carried out on 36 respondents among Staff UiTM Puncak Alam. The findings of this study are important to the industry as it can be used to identify the level understanding about hibah and strengthen the Islamic financial planning in Malaysia.